Analisis Penggunaan Etnopedagogic Pada Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Nur Pangesti Apriliyana; Kusumawati Kusumawati; Ari Rahmi Hasfaraini; Ahmad Siddiq; Novita Yusak Nenogasu (Universitas Sebelas Maret, 2025)
The development of critical thinking skills in elementary schools still faces obstacles due to one-way learning approaches that lack integration with students' local cultural contexts. This study aims to analyze the implementation of ethnopedagogical approaches in enhancing elementary school students' critical thinking skills through the integration of local wisdom values in learning. The study employed a descriptive qualitative approach with research subjects consisting of teachers and 20 elementary school students. Data were collected through learning observations, in-depth interviews, and documentation studies, then analyzed using source triangulation techniques with the Miles and Huberman analysis model. The research findings indicate that the ethnopedagogical approach can enhance students' active involvement in the learning process, with 8 out of 20 students demonstrating good critical thinking abilities in local wisdom materials. Students were more motivated and able to provide rational arguments and draw better conclusions when learning was connected to their local culture, particularly through the use of folktales, traditional games, and local cultural practices. Ethnopedagogy proves effective as an alternative learning approach that not only improves students' critical thinking skills but also strengthens cultural identity and creates more contextual and meaningful learning experiences.Pengembangan keterampilan berpikir kritis di sekolah dasar masih menghadapi kendala karena pembelajaran yang bersifat satu arah dan kurang mengaitkan materi dengan konteks budaya lokal siswa. Penelitian ini bertujuan untuk menganalisis penerapan pendekatan etnopedagogik dalam meningkatkan keterampilan berpikir kritis siswa sekolah dasar melalui integrasi nilai-nilai kearifan lokal dalam pembelajaran. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek penelitian guru dan 20 peserta didik sekolah dasar. Data dikumpulkan melalui observasi pembelajaran, wawancara mendalam, dan studi dokumentasi, kemudian dianalisis menggunakan teknik triangulasi sumber dengan model analisis Miles dan Huberman. Hasil penelitian menunjukkan bahwa pendekatan etnopedagogik mampu meningkatkan keterlibatan aktif siswa dalam proses pembelajaran, dengan 8 dari 20 siswa menunjukkan kemampuan berpikir kritis yang baik pada materi kearifan lokal. Siswa lebih termotivasi dan mampu memberikan argumen yang rasional serta menarik kesimpulan yang lebih baik ketika pembelajaran dikaitkan dengan budaya lokal mereka, terutama melalui penggunaan cerita rakyat, permainan tradisional, dan praktik kebudayaan setempat. Etnopedagogik terbukti efektif sebagai pendekatan pembelajaran alternatif yang tidak hanya meningkatkan keterampilan berpikir kritis siswa, tetapi juga memperkuat identitas budaya dan menghasilkan pembelajaran yang lebih kontekstual dan bermakna.